2014
DOI: 10.1063/1.4894003
|View full text |Cite
|
Sign up to set email alerts
|

In situ transmission electron microscopy of individual carbon nanotetrahedron/nanoribbon structures in Joule heating

Abstract: Collapse of a carbon nanotube results in the formation of a nanoribbon, and a switching of the collapse direction yields a nanotetrahedron in the middle of a nanoribbon. Here, we report in-situ transmission electron microscopy observations of the behavior of carbon nanotetrahedron/nanoribbon structures during Joule heating to reveal their thermal stability. In addition, we propose that the observed process is related to the formation process of the structure. V C 2014 AIP Publishing LLC.[http://dx.doi.org/10.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In order to examine whether our carbon nanotetrahedron/nanoribbon structures can be used for this purpose, we have examined their durability against Joule heating in a transmission electron microscope, and revealed that the nanotetrahedra were as stable as CNTs. 12 When using the carbon nanotetrahedron/nanoribbon structure in flexible devices, it is also important to understand its durability against mechanical strain. In this paper, we focus on the mechanical behavior of the carbon nanotetrahedron/nanoribbon structure under bending.…”
mentioning
confidence: 99%
“…In order to examine whether our carbon nanotetrahedron/nanoribbon structures can be used for this purpose, we have examined their durability against Joule heating in a transmission electron microscope, and revealed that the nanotetrahedra were as stable as CNTs. 12 When using the carbon nanotetrahedron/nanoribbon structure in flexible devices, it is also important to understand its durability against mechanical strain. In this paper, we focus on the mechanical behavior of the carbon nanotetrahedron/nanoribbon structure under bending.…”
mentioning
confidence: 99%